스케일링 건강보험 급여화사업 이후의 스케일링에 관한 인식에 영향을 미치는 요인 - 이경희; Kyeong-hee Lee; 손지영; Ji-young Son; 이행옥; Haeng-ock Lee; 신송희; Song-hee Shin; 전현지; Hyeon-ji Jeon; 유환준; Hwan-jun You; et al. (Han'guk Ch'iwisaeng Hakhoe chi, 2017)
Objectives: The purpose of this study was to examine the recognition about scaling after health insurance benefit business for scaling by national health insurance corporation for the general public. Methods: In order to examine the recognition about scaling after health insurance benefit business for scaling by national health insurance corporation for the general public, study subjects were selected from those who are over 20 years old, living in Seoul and Gyeonggi province since December 2016. Among 300 selected subjects, data of 279 subjects were used for the analysis which is 93% of selected data, except 21 data with insufficient responses. Results: Results of examined factors affecting the recognition about scaling after health insurance benefit business for scaling by national health insurance corporation for the general public show that the recognition about scaling after national health insurance benefit is affected by female (p<0.05), past smoker (p<0.01), exercise more than 3 times a week (p<0.05) and 1-2 times a month (p<0.001) in order. Conclusions: It is necessary to prepare a plan to properly inform the national health insurance benefit for dental scaling and to raise the recognition about the necessity of scaling.